Leptomonas seymouri Co-infection in Cutaneous Leishmaniasis Cases Caused by Leishmania donovani From Himachal Pradesh, India - Thakur, Lovlesh; Kushwaha, Hemant Ritturaj; Negi, Ajeet; Jain, Aklank; Jain, Manju (Frontiers in Cellular and Infection Microbiology, 2020)
Himachal Pradesh in India is a newer endemic state with co-existence of cutaneous and visceral leishmaniasis. The cutaneous leishmaniasis cases are on an increase in the region and reported to be unusually caused by Leishmania donovani with limited molecular validation. In order to molecularly characterize the causative parasite of the cutaneous disease, parasite-specific Internal-Transcribed Spacer 1 (ITS1) PCR RFLP and sequence analysis was performed on skin lesional biopsies from cutaneous leishmaniasis patients. Interestingly, we found the presence of Leptomonas seymouri in 38.5% (22/57) of the patients along with L. donovani detected in all the samples. L. seymouri is a monoxenous insect trypanosomatid, generally incapable of infecting humans. In recent years, the parasite is also reported to co-infect humans with L. donovani in visceral and post kala-azar dermal leishmaniasis (PKDL) cases prevalent in northeastern India. The finding of L. seymouri-L. donovani co-infection in unusual cutaneous cases from Himachal Pradesh is the first ever to our knowledge and implies a newer disease paradigm. There is an urgent need to understand the biology of Leptomonas co-infection with L. donovani and its possible role in visceral and/or dermotropic disease outcome. Importantly, L. seymouri co-infection in cutaneous cases and previously reported visceral and PKDL cases needs to be recognized as a newer phenomenon by the leishmaniasis surveillance program in India.